Bernie for Burlington : the rise of the people's politician and the transformation of one American place - Chiasson, Dan (Alfred A. Knopf, 2026)
"This utterly captivating symphonic story of city, a visionary, and the way our politics changed forever is told through the very specific people of Burlington, beginning with Dan Chiasson's own mall-punk friends of the 1980s: in a video that would go viral decades later in 2020, they engaged with the itinerant carpenter turned socialist mayoral candidate, and there in that food court, the seeds of everything that was Bernie were sown. Dan, uniquely placed to bring a deep insider's perspective, knew all the players: the conservative French-Canadian Catholics whose great grandparents had worked in the mills (his own); the puppeteers and hippies and NYC transplants looking for land and "authenticity" in Vermont; the developers involved in the era's Robert Moses urban-renewal schemes; the corrupt old-school Dems at their table in the local dive; and even Ben and Jerry who became Ben and Jerry's right there in town. They all made up the mosh pit of the Burlington that Bernie captivated, running on the slogan "Burlington is not for sale," to become the modern era's first socialist mayor, intimate with his constituents across workers, cops, lefties, and the little old ladies who organized their streets; he also boasted a foreign policy, a sudden national profile, and a bullhorn to speak to Ronald Reagan. In the tradition of J. Anthony Lukas's Common Ground and the documentary films of Frederick Wiseman, this epic of American city life delves into the gossip--and the exhilaration--around Bernie's unlikely rise, as we watch an American place transformed one diner coffee, one neighborhood door-knock at a time. Full of Sanders himself, reflecting and raging, hitting his themes, forging alliances with all comers, this is a mesmerizing portrait of a politician, a place, and a movement that would change America."-- Provided by publisher.